Antibacterial and electrochemical evaluation of electrospun polyethersulfone/silver composites as highly persistent nanomaterials. Issue 3 (9th December 2022) - Hernández‐Orozco, María Mónica; Castellanos‐Espinoza, Raúl; Hernández‐Santos, Nuri Aranzazú; Ramírez‐Montiel, Fátima Berenice; Álvarez‐Contreras, Lorena; Arellano‐Arreola, Víctor Manuel; Padilla‐Vaca, Felipe; Arjona, Noé; España‐Sánchez, Beatriz Liliana
Abstract: Silver‐based antibacterial nanoparticles have demonstrated indices of possible bacterial resistance after consecutive periods of time, limiting their application on antibacterial surfaces. In this work, we fabricate electrospun composites of polyethersulfone (PES) and silver nanoparticles (AgNPs), displaying highly‐persistent antibacterial behavior after 10 bacterial expositions. The herein‐reported membranes were synthesized by changing the Ag loading (0.05, 0.5, and 5 wt%), adding polyvinylpyrrolidone as a dispersion promoter, and the resulting composites were evaluated after a different number of bacterial expositions against Escherichia coli ( E. coli ) aiming to determine their bacterial tolerance. SEM micrographs revealed that the PES fiber diameters decreased as a function of the silver content from 798 to 398 nm, attributed to the conductivity and the viscosity improvement by AgNPs introduction in the polymer solution during the electrospun process. Moreover, the surface roughness (determined by atomic force microscopy) and the contact angle changed with the Ag content, increasing the hydrophilic behavior and promoting a better interaction with the bacteria suspended in the solution. Antibacterial activity kinetics of PES/AgNPs fibers showed 75% bacterial inhibition against E. coli in the composite with 0.5 wt% Ag after 3 h of exposition, and 75% after 1.5 h in composites with 5 wt% of Ag. The ca. 25% survival bacteria were used for consecutive bacterial tolerance assays, where the antibacterial behavior was constant after 10 expositions. Interestingly, electrochemical tests confirmed that PES fibers could control the silver‐releasing process. Thus, PES/AgNPs composites avoid the bacterial adaptation process, which makes them suitable as functional antimicrobial nanomaterials. Abstract : Electrospun membranes formulated by PES/AgNPs display highly‐persistent antibacterial behavior after consecutive bacterial expositions, which makes them suitable as functional antimicrobial nanomaterials.